Activation of the GABA-alpha receptor by berberine rescues retinal ganglion cells to attenuate experimental diabetic retinopathy - Fang, Wangyi; Huang, Xiaojing; Wu, Kaicheng; Zong, Yuan; Yu, Jian; Xu, Huan; Shi, Jiemei; Wei, Jiaojiao; Zhou, Xujiao; Jiang, Chunhui (Frontiers in Molecular Neuroscience, 2022)
Purpose The aim of this study was to investigate the role and mechanism of berberine (BBR) in the protection of injured retinal ganglion cells (RGCs) in diabetic retinopathy (DR). Methods Experimental diabetic retinopathy rat model was successfully induced by a single intraperitoneal injection of streptozotocin (STZ, 60 mg/kg) in male SD rats with sufficient food and water for 8 weeks. Animals were randomly divided into four groups: (1) non-diabetic, (2) diabetic, (3) diabetic + BBR + PBS, and (4) diabetic + BBR + SR95531. BBR (100 mg/kg) was given daily by gavage to rats in the group (3) and group (4) for 8 weeks, and weekly intravitreal injections were conducted to rats in the group (3) with 5 μL of 1×PBS and rats in the group (4) with 5 μL of GABA-alpha receptor antagonist SR95531 to investigate the underlying mechanisms. The survival and apoptosis of RGCs were observed by fluorescence gold labeling technology and TUNEL staining. Visual function was evaluated by visual electrophysiological examination. Western blotting and immunofluorescence staining were used to analyze the expression of GABA-alpha receptors in RGCs. Results In an animal model, BBR can increase the survival of RGCs, reduce RGCs apoptosis, and significantly improve the visual function. The reduction of GABA, PKC-α, and Bcl-2 protein expression caused by DR can be considerably increased by BBR. SR95531 inhibits BBR's protective effect on RGC and visual function, as well as its upregulation of PKC-α and Bcl-2. Conclusion BBR is a promising preventive or adjuvant treatment for DR complications, and its key protective effect may involve the regulation of RGC apoptosis through the GABA-alpha receptor/protein kinase C-alpha (GABAAR/PKC-α) pathway.